EFFECT OF LIQUID ORGANIC FERTILIZER (LOF) FROM CATFISH SOLID WASTE ON PEAT WATER QUALITY PARAMETERS IN THE CULTIVATION OF CLIMBING PERCH (Anabas testudineus) - Rahel Meriani Siringo Ringo; Saberina Hasibuan; Rodhi Firmansyah (Asian Journal of Aquatic Sciences, 2026)
Liquid organic fertilizer (LOF) derived from the solid waste of catfish processing is a fermented organic product containing macronutrients such as nitrogen (N), phosphorus (P), and potassium (K), as well as micronutrients, amino acids, and decomposer microorganisms that improve water quality. This study aims to analyze the effects of LOF application on peat water quality and the growth performance of climbing perch (Anabas testudineus), and to determine the optimal dosage for cultivation. The research was conducted from June to July 2025 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine, Universitas Riau, with fish rearing carried out in the hatchery using aquarium. The study employed a Completely Randomized Design (CRD) consisting of five treatments: P0 (0 ml/L), P1 (1.5 ml/L), P2 (2 ml/L), P3 (2.5 ml/L), and P4 (3 ml/L), each with three replications. The results showed that water quality parameters remained within acceptable ranges, with temperature of 28.73–28.9°C, pH of 4.96–5.2, TDS of 108.26–124.6 ppm, transparency of 7.66–9.1 cm, DO of 5.23–5.36 mg/L, alkalinity of 17–28 mg/L, nitrate of 4.0045–8.7292 mg/L, and orthophosphate of 1.5397–3.5454 mg/L. The application of POC increased pH, TDS, nitrate, and orthophosphate concentrations. The best growth performance was observed in treatment P2 (2 ml/L), which produced the highest absolute weight gain (2.15 g) and absolute length growth (2.72 cm), while the survival rate reached 100% across all treatments. Therefore, the P2 dosage is considered the most effective treatment for improving peat water quality and enhancing the growth of climbing perch.